JĀZEPS VĪTOLS IN EUROPEAN MUSIC HISTORY. THE AESTHETIC BELIEFS AND STYLE COORDINATES OF THE DISTINGUISHED CLASSICIST (Mūzikas akadēmijas raksti, 2024)
Analysing the creative work of Latvian classic Jāzeps Vītols, the issue of the perception of the composer’s music in the context of broader processes in the past has become more significant. Altogether, in the research interpretation of Vītols’ creative heritage, there is a notable lack of attempts to search for the answer to the question about what place and role does the Latvian classicist hold in Europe and in its entire space of creative thought development that could conclusively be called European music history. How might it be possible to define the creative contribution of Vītols the composer to the dominating aesthetic opinions and characteristic stylistic contexts that were dominant in Europe during his lifetime? While searching for an answer to this question, the author identifies three aspects in this paper.